بحوث المدينة المنورة في العصر الحديث بين الواقع والتطلع - بدر، عبدالباسط بن عبدالرزاق (مركز بحوث ودراسات المدينة المنورة, 2006)
This study presents the main topics of the research works published since the beginning of the Saudi era to the end of the year 1426 H. These research works comprise the historical , cultural, social, economic , educational , informational and constructional studies. They also contain studies in the fields of applied sciences, geology, meteorology , climatology and others . The research aims at revealing the trends of these studies as regards the issues of A1 -Madinah Al - Munawwarah and the extent of their assimilation of the modem developments witnessed by Al - Madinah Al - Munawwarah and their response to the requirements of these developments and the issues that still await further research works .
Keywords: البحث العلمي -- المدينة المنورة